A systematic review on tourism stakeholders’ roles practices towards sustainable tourism using khalifah perspectives - Saffinee, Siti Syahirah; Jamaludin, Mohammad Aizat; Kartika, Betania; Wan Muh Syahrir, Wan Jumanatun Nailiah; Abdul Halim, Sharina (Academic Inspired Network, 2020)
Sustainable tourism (ST) in Islam depends on Khalifah (vicegerent) reacting and practicing Islamic law. Much of the focus on tourism has targeted branding and investing in Islamic tourism. Few systematic reviews on the position practices among Khalifah have been conducted. The present article analyses the existing literature on the roles of tourism stakeholders towards ST. A systematic review of the google scholar and Emerald identified 27 related studies, guided by the Preferred Reporting Items for Systematic Review and Meta Analyses (PRISMA) review method. A review of these papers emerged in three key themes protecting the environment, promoting community engagement, and preserving the social economic climate. Several recommendations for implementing and integrating Khalifah into sustainable tourism are highlighted and provided for potential scholars’ reference in this report.